Pendidikan untuk Semua: Studi pada Kebijakan Wajib Belajar 9 Tahun - Dwi Wulan Sari; Qolbi Khoiri (Departement of Mathematics Education, 2023)
Education is a conscious effort to humanize humans and display a rational and moral human identity. Education in Indonesia is clearly regulated by the national education system and the policies that support it. In the course of the implementation of educational policy through the ups and downs and ins and outs that are so complex and always always become a hot issue in conversation. The nine-year compulsory education is also realized by a global policy of education for all. The nine-year compulsory education policy will further discuss the background, financing, opportunities and even challenges faced by the education sector.